Enzyme Modifications of Red Deer Fat to Adjust Physicochemical Properties for Advanced Applications - Tereza Novotná; Jana Pavlačková; Robert Gál; Ladislav Šiška; Miroslav Fišera; Pavel Mokrejš (Molecules)
Red deer fat makes up approximately 7–10% of the animal’s weight and is not currently used. Regarding sustainability in the food industry, it is desirable to look for opportunities for its processing and use, not only in the food industry. The aim of this study is the enzymatic modification of red deer fat, leading to modification of its physicochemical properties, and the study of changes in phase transitions of modified fat, its structure, color, and texture. Hydrolysis was performed using sn-1,3-specific lipase at different water concentrations (10–30%) and reaction times (2–6 h). The results showed that there was a significant decrease in melting and crystallization temperatures with an increasing degree of hydrolysis, which was confirmed by differential scanning calorimetry. FTIR spectra revealed a decrease in the intensity of the ester bonds, indicating cleavage of triacylglycerols. Texture analysis of the modified fats confirmed a decrease in hardness of up to 50% and an increase in spreadability. The color parameter values remained within an acceptable range. The results show that enzymatic modification is an effective tool for targeted modification of red deer fat properties, and this expands the possibilities of its application in cosmetic matrices and food applications as functional lipids.